Die verhouding tussen integrasie- teorie en konflikteorie - Louw, A. D. (Koers, 1983)
The author bases his article on a comparison and evaluation of the contributions of conflict theoreticians and consensus theoreticians in dealing with the phenomenon of social conflict. He looks in some detail at the development of conflict theory, and analysis the views of especially Parsons in this regard. The author is of the opinion, however, that pure conflict theory in sociology, in so far as it manifests itself as an alternative orientation with regard to structural functionalism, should be rejected. He posits the view that there is nothing within the conceptual apparatus of conflict theory which clashes with integration theory, and he accepts the view of Dahrendorf who sees integration theory and conflict theory as applicable in certain situations and their particular demands. He feels that the opposition between the integration model and the conflict model is unfounded.